Isolasi dan Identifikasi Asam Klorogenat dari Ampas Kopi Menggunakan Ekstraksi Cair–Cair dan Kromatografi Kolom dengan Analisis HPLC - Samsul Bahri; Najib Muhammad; Fahmi Aryanu (Lembaga Publikasi Ilmiah Nusantara, 2025)
Spent coffee grounds represent an abundant agro-industrial waste that still contain valuable phenolic compounds, particularly chlorogenic acid (CGA), yet remain largely underutilized. This study aimed to isolate and tentatively identify CGA from Arabica spent coffee grounds using a stepwise separation approach. Dried coffee grounds were extracted by maceration with 70% ethanol. The resulting crude extract was subsequently fractionated by liquid–liquid extraction using an ethyl acetate–water solvent system to separate components based on polarity. The polar fraction was further purified by silica gel column chromatography employing a gradient elution system. Selected fractions were monitored by thin-layer chromatography (TLC) and analyzed by high-performance liquid chromatography (HPLC) using a C18 column with UV detection at 325 nm. HPLC analysis revealed a dominant peak with a retention time consistent with that of a chlorogenic acid standard analyzed under identical chromatographic conditions, accompanied by a relatively symmetrical peak profile. Based on this chromatographic behavior, the isolated compound was tentatively identified as chlorogenic acid. Quantitative determination using an external standard calibration curve indicated that the CGA content in the selected fraction ranged from 18 to 20 mg per gram of dry extract. Overall, the combination of ethanol extraction, liquid–liquid fractionation, column chromatography, and HPLC analysis provides an effective and reproducible approach for obtaining CGA-enriched fractions from spent coffee grounds and supports the valorization of coffee waste as a sustainable source of bioactive phenolic compounds.